2016
DOI: 10.1017/s2045796015001110
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of Geriatric Depression Scale scores in older Australian and Japanese women

Abstract: Significantly more Japanese women scored within the mild and moderate ranges on the GDS compared with their Australian peers, even when controlling for possible confounding factors. Of the lifestyle and health factors assessed in this analysis no single variable was a common risk factor for higher depressive scores for both countries. The presence of cultural influences that may impact the risk of experiencing depressive symptoms, and culture specific patterns of item endorsement on depressive symptom measures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 37 publications
(75 reference statements)
2
7
4
Order By: Relevance
“…This result indicates that depressive symptoms among people from Japan and Australia with similar levels of pain from knee OA are equivalent. This is in contrast to a previous study that demonstrated signi cantly higher depressive symptoms using the Geriatric Depression Scale in community-dwelling older Japanese than Australians, even after controlling for lifestyle and health factors associated with depressive symptoms [20]. Mean scores were notably low in both cohorts (4.9 and 4.2 out of 42 for participants from Japan and Australia respectively).…”
Section: Depressive Symptomscontrasting
confidence: 99%
See 2 more Smart Citations
“…This result indicates that depressive symptoms among people from Japan and Australia with similar levels of pain from knee OA are equivalent. This is in contrast to a previous study that demonstrated signi cantly higher depressive symptoms using the Geriatric Depression Scale in community-dwelling older Japanese than Australians, even after controlling for lifestyle and health factors associated with depressive symptoms [20]. Mean scores were notably low in both cohorts (4.9 and 4.2 out of 42 for participants from Japan and Australia respectively).…”
Section: Depressive Symptomscontrasting
confidence: 99%
“…This meant that participants' levels of depressive symptoms were limited to the normal to moderate range [38], which may have in uenced the ndings. The lower BMI and better physical functioning among the participants from Japan may explain lower than expected levels of depressive symptoms relative to the comparison group, and the contrast between our ndings and the previous comparison [20].…”
Section: Depressive Symptomscontrasting
confidence: 96%
See 1 more Smart Citation
“…This finding was consistent with Turkish (7,31) and in the Australian studies (31). However, in Japanese and Pakistani studies, employment was not a significant predictor for the probability of depressive symptoms (31)(32)(33). These findings are consistent with an established association between various sources of support in occupational life and depression.…”
Section: Discussionsupporting
confidence: 86%
“…Working status is a significant factor that was related to the occurrence of depressive symptoms in the LR model (OR=1.47). This finding was consistent with Turkish (7,31) and in the Australian studies (31). However, in Japanese and Pakistani studies, employment was not a significant predictor for the probability of depressive symptoms (31)(32)(33).…”
Section: Discussionsupporting
confidence: 86%